Combination of transparent full-area encapsulation and non-transparent edge encapsulation with high getter content

By using a combination package of high transparency first adhesive and a high water absorption second adhesive on the organic electronic device, the problem of water vapor and oxygen permeability in the narrow edge electronic structure is solved, extending the service life and maintaining the optical characteristics.

CN112424970BActive Publication Date: 2025-01-07TESA SE
View PDF 29 Cites 0 Cited by

Patent Information

Application Number
CN201980034581.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-05-24
Filing Date
2019-04-26
Publication Date
2025-01-07
Estimated Expiration
2039-04-26

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prevent water vapor and oxygen from penetrating, especially in narrow-edge electronic structures, resulting in a shortening of service life without damaging the optical characteristics of organic electronic devices.

Method used

The first adhesive is used to cover the organic electronic device with a transparency of more than 80% and a haze of less than 5%, and apply a second adhesive to the periphery to form an edge package. The second adhesive has a water absorption capacity of more than 5%, and the edge package width does not exceed 2mm, combining transparent full-zone package with high water absorption capacity non-transparent edge package.

Benefits of technology

It improves the utilization rate of the permeability barrier, effectively prevents moisture penetration, extends the service life of the organic electronic structure, and maintains the transparency of optical properties and high water absorption properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112424970B_ABST
    Figure CN112424970B_ABST
Patent Text Reader

Abstract

An organic electronic structure comprising a substrate, an organic electronic device arranged on the substrate, and a cover at least partially covering the organic electronic device and at least partially adhered to the substrate and / or the electronic device, wherein the structure further comprises: at least one layer of a first adhesive, the first adhesive at least partially covering the organic electronic device and having a transparency greater than 80% and a haze less than 5%; and at least one layer of a second adhesive, the at least one layer of the second adhesive surrounding the at least one layer of the first adhesive on the periphery of the at least one layer of the first adhesive, so that the at least one layer of the second adhesive forms an edge encapsulation, wherein the width of the edge encapsulation using the second adhesive does not exceed 2 mm, and wherein the second adhesive has a water absorption capacity greater than 5% by weight. This design allows the width of the edge area around the display or other organic electronic structure to be smaller.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for protecting an organic electronic device arranged on a substrate, the method comprising the steps of applying a cover on the organic electronic device in such a way that the cover at least partially covers the organic electronic device, and adhering the cover with at least one layer of a first adhesive and at least one layer of a second adhesive. The present invention also relates to an organic electronic structure, comprising a substrate, an organic electronic device arranged on the substrate, and at least partially covering the organic electronic device and at least partially (partially) covering the organic electronic device. ) is a cover adhered to a substrate and / or an organic electronic device. Background Art

[0002] (Opto) electronic devices are increasingly used in commercial products. Such devices include organic or inorganic electronic structures, such as organic, organometallic or polymer semiconductors and combinations thereof. Depending on the desired application, these devices and products can be designed to be rigid or flexible, wherein there is an increased demand for flexible devices. The manufacture of such devices is carried out, for example, by means of printing processes such as relief printing, gravure printing, screen printing, lithography or so-called "non-impact printing" such as thermal transfer printing, inkjet printing or digital printing. However, in many cases, vacuum processes such as chemical vapor deposition (CVD), physical vapor deposition (PVD), plasma-enhanced chemical or physical deposition (PECVD), sputtering, (plasma) etching or evaporation are also used, wherein a mask is usually used for structuring.

[0003] Examples of (opto)electronic applications which are already commercially available or have great market potential include electrophoretic or electrochromic structures or displays, organic or polymer light-emitting diodes (OLED or PLED) in advertising and display devices or as lighting, electroluminescent lamps, light-emitting electrochemical cells (LEEC), organic solar cells, preferably dye or polymer solar cells, inorganic solar cells, preferably thin-film solar cells, in particular those based on silicon, germanium, copper, indium or selenium, organic field effect transistors, organic switching elements, organic optical amplifiers, organic laser diodes, organic or inorganic sensors or RFID transponders based on organic or inorganic elements.

[0004] In the present description, an organic (opto)electronic device is therefore understood to mean an electronic device which comprises at least one at least partially organic component having an electronic function, for example an organometallic compound.

[0005] In the field of inorganic and / or organic (opto)electronics, but in particular in the field of organic (opto)electronics, a technical challenge for achieving adequate service life and functionality of (opto)electronic devices is to protect the components contained therein from permeants. The permeants may be various low-molecular organic or inorganic compounds, in particular water vapor and oxygen.

[0006] In the field of inorganic and / or organic (opto)electronics, more particularly in the case of the use of organic raw materials, many (opto)electronic devices are sensitive both to water vapor and oxygen, wherein the penetration of water or water vapor is considered a major problem for many devices. Therefore, during the service life of the electronic device, protection by means of encapsulation is required, since otherwise the performance degrades over the time of use. For example, oxidation of components can lead within a very short time to a significant reduction in brightness for light-emitting devices such as electroluminescent lamps (EL lamps) or organic light-emitting diodes (OLEDs), to a significant reduction in contrast for electrophoretic displays (EP displays) or to a significant reduction in efficiency for solar cells.

[0007] It has been proven that full-area (full, ) packaging, the adhesive or tape completely covers the organic electronic structure applied to the substrate and the edge area and connects this area to the impermeable cover. In the case of light-emitting or light-consuming structures, the adhesive layer must be highly transparent and have little light scattering (haze).

[0008] In order to achieve a long service life of the structure, it is advantageous to provide the adhesive with a trapping agent material, such as a desiccant, in order to achieve a barrier effect against penetrating permeates.

[0009] To characterize the barrier effect, the oxygen transmission rate OTR (Oxygen Transmission Rate) and the water vapor transmission rate WVTR (Water Vapor Transmission Rate) are usually specified. In this case, the corresponding ratios express the area- and time-dependent flow of oxygen or water vapor through the film under specific temperature and partial pressure conditions and optionally other measuring conditions (e.g. relative humidity). The lower these values ​​are, the better the corresponding material is suitable for packaging. In this case, the index of permeation is not only based on the value of WVTR or OTR, but also always includes an index of the average path length of the permeation, such as the thickness of the material, or standardization to a specific path length.

[0010] The permeability P is a measure of the permeability of an object to gases and / or liquids. Low P values ​​characterize a good barrier effect. The permeability P is a specific value for a defined material and a defined permeate under steady-state conditions at a specific permeation path length, partial pressure and temperature. The permeability P is the product of the diffusion term D and the solubility term S: P = D·S.

[0011] The solubility term S mainly describes the affinity of the barrier adhesive composition for the permeate. For example, in the case of water vapor, low S values ​​are reached for hydrophobic materials. The diffusion term D is a measure of the mobility of the permeate in the barrier material and depends directly on properties such as molecular mobility or free volume. Relatively low D values ​​are often reached for strongly crosslinked or highly crystalline materials. However, in general, highly crystalline materials are not so transparent, and stronger crosslinking leads to lower flexibility. The permeability P often increases with increasing molecular mobility, for example even at elevated temperatures or above the glass transition temperature.

[0012] The method of improving the barrier effect of the adhesive composition must take into account the two parameters D and S in particular with regard to the influence on the permeability of water vapor and oxygen. In addition to these chemical properties, the role of physical influences on the permeability must also be taken into account, in particular the average permeation path length and the interfacial properties (flow behavior, adhesion of the adhesive composition). An ideal barrier adhesive composition has low D and S values ​​and very good adhesion to the substrate.

[0013] A low solubility term S is usually not sufficient alone to achieve good barrier properties. In particular, a typical example is silicone elastomer. This material is extremely hydrophobic (small solubility term), but has a relatively low barrier effect for water vapor and oxygen due to its freely rotatable Si-O bonds (large diffusion term). For a good barrier effect, a good balance between the solubility term S and the diffusion term D is also necessary.

[0014] However, if efficient particulate desiccants such as calcium oxide or zeolites are used to achieve good barrier properties, this results in increased haze, which is problematic for light-emitting or light-consuming structures as described above. Due to the high refractive index of these desiccants (calcium oxide: 1.86), the haze is already significantly greater than 5% at a proportion of 2 wt % for conventional encapsulation adhesive compositions. Transparent and anti-fog desiccants such as silanes are known, but are less efficient.

[0015] As an alternative to full-area encapsulation, edge encapsulation can also be used to maintain transparency in the relevant area of ​​the structure, wherein only the area surrounding the electronic structure is provided with the encapsulation adhesive composition. Since no special optical requirements need to be met in the edge area, it can be filled with an efficient desiccant. The disadvantage here is the remaining cavity in the encapsulated structure. Therefore, arrangements are also known in which edge encapsulation and full-area encapsulation are combined.

[0016] Edge sealing with a sealant is known, for example, from WO 2009085736. This patent discloses a solar panel which is covered over the entire area with a desiccant-free adhesive layer and which is sealed at the edges with a desiccant-containing sealing material which is applied in liquid form from a melt.

[0017] US2008 / 0289681 A1 discloses a solar cell module, wherein the solar cell is applied to a substrate via a casting composition layer. The solar cell is covered by a transparent cover layer via another casting composition layer. The module may also have an edge encapsulation containing a desiccant, the width of which is 5-20 mm. Zeolite is used as a desiccant. Preferred embodiments of the edge encapsulation are hot melt films and hot melt pastes.

[0018] US 6,936,131 B2 describes the use of transfer tapes filled with desiccants, which can be used as full-area encapsulation or edge encapsulation. Inorganic particles are described as desiccants. The particles used in the examples lead to high haze in the adhesive composition.

[0019] US20070013292A1 discloses an organic electronic structure provided with an edge package containing a desiccant. The edge package can be designed as a curable adhesive or as an adhesive tape. The width of the edge package is preferably designed to be greater than 2 mm.

[0020] In the field of mobile electronic devices, a trend towards narrower and narrower edges around displays is observed. The web width of the adhesive area outside the active area usually does not exceed 2 mm. In such devices, the performance limits of highly transparent and almost light-free encapsulation adhesives are reached and the service life is no longer sufficient because the short distance from the environment to the active area is traversed by penetrants, especially water vapor, in too short a time and then leads to destruction. This period of time is called the lag time.

[0021] Furthermore, these smaller web widths present difficulties in terms of tolerances in use: the edge encapsulation containing desiccant, which is arranged outside the active surface (i.e., the active area), must not in any case protrude into the active surface or flow into it during use. Therefore, for reasons of tolerance, the entire, already small web width cannot be used for efficient edge encapsulation. Summary of the invention

[0022] The object of the present invention is therefore to provide an improved encapsulation of narrow-edge organic electronic structures, which allows improved utilization of the narrow edges as a permeation barrier and thus better protection of the encapsulated object from moisture penetration without causing impairment of the optical properties of the organic electronic structure.

[0023] The object is achieved with a protection method of the type mentioned at the outset in that at least one layer of a first adhesive at least partially covers the organic electronic device and has a transparency of more than 80% and a haze of less than 5%, and at least one layer of a second adhesive surrounds at least one layer of the first adhesive at its periphery, so that the at least one layer of the second adhesive forms an edge encapsulation, wherein the width of the edge encapsulation with (with) the second adhesive does not exceed 2 mm (i.e. 2 mm or less), and wherein the second adhesive has a water absorption capacity of more than 5% by weight, i.e. a water absorption amount of

[0024] In addition, according to the present invention, an organic electronic structure of the above type is provided, wherein the structure also has at least one layer of a first adhesive and at least one layer of a second adhesive, wherein the first adhesive at least partially covers the organic electronic device and has a transparency greater than 80% and a haze less than 5%, and at least one layer of the second adhesive surrounds at least one layer of the first adhesive on the periphery of the at least one layer of the first adhesive, so that the at least one layer of the second adhesive forms an edge encapsulation, wherein the width of the edge encapsulation using (having) the second adhesive does not exceed 2 mm, and it has a water absorption capacity greater than 5 weight %.

[0025] A first transparent full-area encapsulation is thereby combined with a second (non-transparent) edge encapsulation having a high water absorption capacity.

[0026] Preferred embodiments of the method and of the organic electronic structure are contained in the dependent claims. Preferred embodiments of the method apply analogously to the organic electronic structure and vice versa.

[0027] Preferred are designs of the organic electronic structure in which no further polymer layers are present between the cover and the organic electronic device, ie only at least one layer of the first adhesive, in particular only one layer of the first adhesive, is a polymer layer and no further layers are present.

[0028] A polymer is a compound generally consisting of organic chain or branched molecules (macromolecules), which consist of identical, similar or different units (so-called monomers). In the simplest case, a macromolecule consists of only one type of monomer. Copolymers consist of various monomers which are randomly distributed in the macromolecule, regularly distributed or can be present in block form. A polymer contains at least three identical monomer units. A monomer unit within the meaning of this definition is the combined form of monomers in a polymer.

[0029] Structures in which the organic electronic device is located directly on a substrate are also particularly advantageous.

[0030] Likewise, structures are particularly advantageous in which the organic electronic device arranged on the substrate is already provided with a primary encapsulation, for example a thin-film encapsulation, and the method claimed here is carried out as a secondary encapsulation on one or both sides of the electronic device arranged on the substrate.

[0031] The cover at least partially covers the organic electronic device. It preferably completely covers the organic electronic device.

[0032] The at least one layer of the first adhesive at least partially covers the organic electronic device. It preferably completely covers the organic electronic device.

[0033] Preferred is a structure in which the second adhesive does not contact or cover the organic electronic device, i.e. a structure in which the second adhesive is applied at a distance from the organic electronic device. The distance at which the adhesive is applied relative to the organic electronic device is preferably 0.1 mm to 2 mm, in particular 0.2 mm to 1 mm, particularly preferably 0.2 mm to 0.5 mm.

[0034] In a preferred embodiment, the distance formed in this way is filled with the first adhesive. If the organic electronic device is surrounded by a primary encapsulation, in another preferred embodiment, the distance is filled with the material of the primary encapsulation. In another preferred embodiment, the distance is filled with the material of the primary encapsulation and the first adhesive.

[0035] The adhesive can be present as a liquid or pasty adhesive or in the form of an adhesive tape. An adhesive tape is particularly preferably used because it allows good, ie particularly precise and particularly simple, application of the adhesive.

[0036] The thickness of the adhesive layer of the first or second adhesive is preferably between about 4 μm and about 250 μm. The adhesive thickness is particularly preferably not more than 50 μm, in particular not more than 25 μm.

[0037] In principle, any adhesive described in the prior art (e.g., in G.habenicht: Kleben, 6th edition, Springer 2009) can be used as adhesive. Without wishing to unnecessarily restrict the invention, examples of such adhesives are those based on vinyl acetate, polyvinyl alcohol, polyvinyl acetal, polyvinyl chloride, (meth) acrylates, polyamides and copolymers thereof, cellulose, urea, melamine resins, phenolic resins, epoxides, polyurethanes, polyesters, polyaromatic compounds, chloroprene, nitrile rubber, styrene, butyl rubber, polysulfides or silicones. Mixtures are also according to the invention. Preferably, an activatable adhesive is used.

[0038] The first adhesive is preferably a pressure-sensitive adhesive. It is particularly preferred to use an activatable pressure-sensitive adhesive. The first adhesive is more preferably present as a pressure-sensitive adhesive tape. This simplifies the processing of the adhesive.

[0039] Pressure-sensitive adhesives are adhesives which allow permanent bonding to substrates even under relatively weak pressure and which can be peeled off from the substrate again after use essentially without residue. Pressure-sensitive adhesives function as permanent pressure-sensitive adhesives at room temperature, that is, have sufficiently low viscosity and high touch tack so that they wet the surface of the corresponding adhesive substrate even under low touch pressure. The adhesive properties of the adhesive composition are based on its adhesive properties, while the re-peelability is based on its cohesive properties. Various compounds can be used as the basis for pressure-sensitive adhesives.

[0040] All pressure-sensitive adhesives known to the person skilled in the art can be used as pressure-sensitive adhesives, i.e. for example those based on acrylates and / or methacrylates, polyurethanes, natural rubber, synthetic rubbers, styrene block copolymer compositions with elastomeric blocks consisting of unsaturated or hydrogenated polydiene blocks (polybutadiene, polyisoprene, copolymers of both and other elastomeric blocks familiar to the person skilled in the art), polyolefins, fluoropolymers and / or silicones. This also includes other compositions with pressure-sensitive adhesive properties according to the "Handbook of Pressure Sensitive Adhesive Technology" by Donatas Satas (Satas & Associates, Warwick 1999).

[0041] Activatable adhesives are considered to be adhesive systems in which the final bond is produced by input of energy, for example by actinic radiation or heat.

[0042] In principle, all customary activation-bonding adhesive composition systems can be used as activatable adhesive compositions. Activation is usually carried out by energy input, for example by actinic radiation, heat or mechanical energy, such as ultrasound or friction.

[0043] Heat-activatedly bonding adhesive compositions can be divided into two categories: thermoplastic heat-activatedly bonding adhesive compositions (hotmelt adhesives) and reactive heat-activatedly bonding adhesive compositions (reactive adhesives). This classification also includes those adhesive compositions that can be classified into both categories, namely reactive thermoplastic heat-activatedly bonding adhesive compositions (reactive hotmelt adhesives).

[0044] Thermoplastic adhesives are based on polymers which soften reversibly when heated and solidify again when cooled. As thermoplastic adhesive compositions, those based in particular on polyolefins and copolymers of polyolefins and their acid-modified derivatives, ionomers, thermoplastic polyurethanes, polyamides and polyesters and their copolymers and block copolymers such as styrene block copolymers have proven to be advantageous.

[0045] In contrast, the adhesive of reactive heat activated bonding comprises reactive components. The latter component is also referred to as "reactive resin", wherein the crosslinking process is initiated by heating, which ensures a lasting, stable connection after the crosslinking reaction ends. This adhesive composition preferably also comprises an elastic component, such as synthetic nitrile rubber or styrene block copolymer. This elastic component is due to its high flow viscosity and is given even under pressure a particularly high dimensional stability for the adhesive composition of heat activated bonding.

[0046] Radiation-activated adhesive compositions are also based on reactive components. The latter component may include, for example, a polymer or a reactive resin, wherein a crosslinking process is initiated by irradiation, which ensures a durable, stable connection after the crosslinking reaction has ended. Such adhesive compositions preferably also contain an elastic component as described above.

[0047] Radiation-activatable pressure-sensitive adhesives differ from radiation-crosslinked pressure-sensitive adhesives in that the pressure-sensitive adhesive properties are set by radiation crosslinking during the production of the adhesive tape. For radiation-activatable pressure-sensitive adhesives, the radiation activation takes place during the application process. After radiation activation, the adhesive composition is generally no longer pressure-sensitively adhesive.

[0048] Activatable pressure-sensitive adhesive tapes also include pressure-sensitive adhesive tapes assembled from two or more adhesive films, such as those disclosed in DE 10 2013 222739 A1. The two or more adhesive films are activated by contacting them.

[0049] Particularly suitable are those activatable (pressure-sensitive) adhesive compositions which are prepared from compounds having at least one of the following functional groups: epoxy groups, amines, urea groups, hydroxyl groups, ether groups, acid groups, in particular carboxylic acid groups, preferably acrylic and methacrylic acid groups, and also carboxylic anhydride groups, ester groups and amide groups, isocyanates, imidazoles, phenolic groups, urea groups, silane groups, olefinic double bonds, in particular in combination with initiator groups which can initiate free-radical polymerization, or in combination with sulfur-containing vulcanizing agents.

[0050] The activatable (pressure-sensitive) adhesive composition may optionally contain one or more additional formulation ingredients, such as hardeners, reaction accelerators, catalysts, initiators, fillers, microspheres, tackifier resins, non-reactive resins, plasticizers, adhesives, asphalts, anti-aging agents (antioxidants), light screens, UV-absorbers, rheological additives and other auxiliaries and additives.

[0051] Examples of (barrier) adhesive compositions particularly suitable for the present invention can be found in US 2006 / 0100299 A1, WO 2007 / 087281 A1, EP 2166593 A1, EP 2279537 B1, EP 2465149 B1, EP 2768919 B1, EP 2768918 A1, EP 2838968 A1, EP 2838968 A1 or WO 2016066435 A1, wherein this list is purely exemplary and by no means exhaustive.

[0052] The second adhesive can likewise be a pressure-sensitive adhesive composition and can also be designed as a pressure-sensitive adhesive tape. However, it is particularly preferred that the second adhesive is designed as a liquid adhesive.

[0053] The second adhesive preferably contains a desiccant. However, the water absorption properties can also be attributed to the adhesive itself. As an example, an epoxide which has not yet completely reacted is mentioned here.

[0054] In principle, all desiccants familiar to the person skilled in the art can be used as desiccants in the second adhesive. If desiccants are also used in the first adhesive, these desiccants are preferably those which do not impair or only slightly impair the transparency of the adhesive.

[0055] Water vapor penetrating into the (opto)electronic arrangement then binds chemically or physically, preferably chemically, to these substances and thereby increases the penetration time ("lag time"). Desiccants are referred to in the literature as "getters", "scavengers", "desiccants" or "absorbers". In the following, only the expression "desiccant" is used. The binding of the penetrating water takes place either physically, typically by adsorption onto silicon dioxide, molecular sieves, zeolites or sodium sulfate. Chemically, for example via alkoxysilanes, Oxazolidines, isocyanates, barium oxide, phosphorus pentoxide, alkali metal and alkaline earth metal oxides (e.g. calcium oxide), metallic calcium or metal hydrides are used to bind water (WO 2004 / 009720 A2). However, many fillers are not suitable for transparent bonding of displays, for example, with the first adhesive composition, because the transparency, in particular the haze, of the adhesive composition is reduced.

[0056] In adhesives, desiccants described as such are primarily inorganic fillers, such as calcium chloride or various oxides (see US 5,304,419 A, EP 2 380 930 A1 or US 6,936,131 A). Such adhesive compositions predominate in edge encapsulation, i.e. in cases where only the edges are bonded. However, adhesive compositions with such getters are not suitable for full-area encapsulation, since, as detailed above, they reduce transparency.

[0057] Organic getters are also described in adhesive compositions. For example, in EP 2 597 697 A1, polymer alkoxysilanes are used as desiccants. Many different silanes are mentioned in WO 2014 / 001005 A1 as desiccants in adhesive compositions. According to this document, the maximum amount of desiccant to be used is 2% by weight, because the sensitive electronic structures to be encapsulated will be damaged if a higher proportion of the substance is used. The problem is that the organic desiccants used are usually very reactive and cause damage (so-called "dark spots") when in contact with sensitive organic electronic devices in full-area encapsulation. Therefore, adhesive compositions with such desiccants are preferably suitable for edge encapsulation (second adhesive composition), in which there is no direct contact between the adhesive composition and the electronic device.

[0058] Preferably, a desiccant with a water absorption capacity of more than 10% by weight, particularly preferably more than 20% by weight, is used. As a result, the proportion of desiccant in the adhesive composition can be kept low, thereby reducing impairment of the technical adhesive properties.

[0059] Calcium oxide is particularly preferred as a desiccant. It has a high water absorption of over 20% by weight, absorbs water slowly enough so that the drying capacity is largely retained during the adhesive manufacturing process, and binds water without changing its physical form (i.e., without liquefying, for example).

[0060] The desiccant content of the second adhesive is preferably 15% by weight or more, particularly preferably 30% by weight or more. In the case of further preferred adhesive compositions with a desiccant content of 40% by weight or more, an embodiment in the form of a liquid adhesive is preferred because the high filler content impairs the pressure-sensitive adhesiveness of the adhesive tape.

[0061] The two aforementioned embodiments are very particularly preferably combined. The adhesive thus preferably has a desiccant content of greater than 20% by weight, wherein the water absorption of the desiccant is greater than 10% by weight, particularly preferably greater than 20% by weight.

[0062] Particularly preferred are second adhesives which contain a desiccant and have a water absorption of more than 5% by weight, in particular more than 10% by weight, very particularly more than 14% by weight.

[0063] The first adhesive preferably also has water absorbing properties, preferably as the first adhesive for full area encapsulation contains in particular a water scavenger Usually a desiccant.

[0064] The first adhesive preferably contains less than 2 wt % of particulate desiccant, in particular calcium oxide, since due to the high refractive index of many desiccants (calcium oxide: 1.86), in conventional encapsulating adhesive compositions the haze is usually already greater than 5 wt % at a proportion greater than 2 wt %.

[0065] Preferably, the base adhesive composition of the first adhesive and / or the second adhesive, ie the adhesive composition formulation without the optional addition of a desiccant, has a relative humidity of less than 100 g / m 2 d(g / m 2 The water vapor transmission rate (WVTR) of 50 μm / day is preferably less than 20 g / m 2 d. Preferred are adhesive compositions based on polybutenes such as butyl rubber, in particular based on modified or unmodified polyisobutylene.

[0066] Examples of such adhesive compositions are: WO2013057265 (copolymers of isobutylene or butene), DE102008047964A1 (vinyl aromatic block copolymers), US8557084B2 (crosslinked vinyl aromatic block copolymers), EP2200105 (polyolefins), US8460969B2 (butylene block copolymers), WO2007087281A1 (hydrogenated cycloolefin polymers with PIB), WO2009148722 (PIB with acrylate reactive resin), EP2502962A1 (PiB-epoxide), JP2015197969 (PIB).

[0067] The first adhesive (full-area encapsulation adhesive composition) and the second adhesive (edge ​​encapsulation adhesive composition) are preferably based on the same basic adhesive composition. This means that the components of the adhesive composition that are dominant in terms of the adhesive technology properties are essentially the same, and it is particularly advantageous that the components are also used in essentially the same quantitative ratios. In particular, the base polymer or base polymers of the two adhesive compositions are the same.

[0068] In the present context, "base adhesive composition", "based on ..." or "based on ..." means that the properties of the adhesive composition are at least largely determined by the basic properties of the base adhesive composition or one or more base polymers or monomers, wherein it is of course not excluded that these are additionally influenced by the use of modifying auxiliaries or additives or other polymers or monomers in the composition. In particular, this can mean that the proportion of the base polymer or base polymers and optionally monomers in the total mass of the polymer phase is greater than 50% by weight.

[0069] In the transparent first adhesive, a desiccant is preferably one which has a refractive index similar to that of a typical encapsulating adhesive and thus enables a highly transparent adhesive composition. Similar refractive indices are understood to mean that the difference in refractive index between the first adhesive and the desiccant is not greater than 0.02. It is particularly preferred to use hydrotalcite as a desiccant. For example, synthetic hydrotalcite (Mg6Al2(CO3)(OH) from Sigma-Aldrich) 16 4H2O, product number 652288) is very suitable.

[0070] In particular, the full-area first adhesive is preferably free of particulate fillers since they can increase haze.

[0071] The transparent first adhesive preferably includes a molecularly dispersed desiccant.

[0072] The first adhesive is preferably applied as a sheet-like structure (adhesive tape) and the second adhesive is applied as a liquid adhesive.

[0073] According to the invention, the method further comprises: first applying the first adhesive as a tape to the electronic device (which is usually arranged on a substrate) or its cover, and then applying the liquid adhesive as a second adhesive around the electronic device. Finally, the electronic device and the cover are joined, wherein the first adhesive composition acts as a spacer (gasket, Abstandhalter) and significantly reduces the extrusion of the second adhesive composition.

[0074] The width of the edge encapsulation using the second (encapsulation) adhesive is preferably no more than 2 mm, very particularly preferably less than 1 mm, since this maximizes the ratio of active area to total area of ​​the electronic structure. In the case of displays, for example, users find such structures particularly visually appealing.

[0075] The specific combination of two adhesives according to the invention makes it possible to provide acceptable lag times for organic electronic structures even with very small edge widths in the range of not more than 2 mm. BRIEF DESCRIPTION OF THE DRAWINGS

[0076] Figure 1 A calcium test is shown as a measure for determining the service life of an electronic structure. Figure 2 A curve obtained from measured data of a test is shown by way of example. Figure 3 The breakthrough time as a function of the water scavenger content is shown exemplarily. Figures 4 to 6 Three embodiments of the organic electronic structure according to the invention are shown in FIG. 1 , each of which is preferred in itself. Figure 4 An organic electronic structure is shown in a simplified form with an organic electronic device applied to a substrate and a cover applied by means of two adhesive compositions; Figure 5 An organic electronic structure is shown, which has Figure 4 In addition to the basic components of the structure shown in FIG. 1 , there is also a primary package and a secondary cover; and Figure 6 An organic electronic structure is shown, which has Figure 4 In addition to the basic components of the structure shown in FIG, there is also a primary package.

[0077] in:

[0078] 1: Organic electronic structures

[0079] 2: Base

[0080] 3: Organic electronic devices

[0081] 4: Covering

[0082] 5: First Adhesive

[0083] 6: Second adhesive

[0084] 7: Primary packaging, such as thin layer packaging

[0085] 8: A second covering is arranged on the surface of the structure opposite to the first covering.

[0086] Figure 4 The organic electronic structure 1 shown in the figure comprises an organic electronic device 3 applied to a substrate 2. The organic electronic device 3 is completely surrounded by a second adhesive 6, or more precisely, at a certain distance from the organic electronic device 3. The second adhesive 6 has good water absorption capacity. The organic electronic device 3 is covered by a first adhesive 5. The first adhesive also fills the distance (gap) between the organic electronic device 3 and the second adhesive 6. The layer of the first adhesive 5 has a transparency of more than 80%, so as not to impair the function of the organic electronic device 3 below.

[0087] Figure 5 The organic electronic structure 1 shown in FIG. 1 corresponds in its basic structure to Figure 4 In addition, it comprises a primary package 7. For example, the primary package can be a thin layer package. Figure 5 The primary encapsulation 7 shown in FIG. 1 completely covers the organic electronic device 3 and also fills the gap between the second adhesive 6 and the organic electronic device 3. Finally, the organic electronic structure also has a second cover 8 arranged on the face of the structure opposite to the first cover 4.

[0088] Figure 6 The organic electronic structure 1 shown in FIG. 1 corresponds in its basic structure to Figure 4 In addition, it comprises a primary package 7. For example, the primary package can be a thin layer package. Figure 5 The primary package 7 shown in FIG. 1 completely covers the organic electronic device 3 and fills a partial area of ​​the gap between the second adhesive 6 and the organic electronic device 3. The other partial areas of the gap are filled by the first adhesive. The second adhesive is adhered to at least a partial area of ​​the primary package. DETAILED DESCRIPTION

[0089] Measurement method:

[0090] Unless otherwise stated, the measurements were carried out under test conditions of 23±1° C. and 50±5% relative air humidity.

[0091] Water Vapor Permeability Rate (WVTR):

[0092] The WVTR is measured in accordance with ASTM F-1249-13 at 38° C. and 90% relative humidity. In each case, the determination is carried out twice and the average value is obtained. The values ​​given are standardized to a thickness of 50 μm. For the measurement, the adhesive composition, in particular the transfer tape, is attached to a highly permeable polysulfone membrane (available from Sartorius), which itself does not contribute to any permeation barrier.

[0093] Water absorption capacity of adhesive composition:

[0094] After storage of the samples at 23° C. and 50% relative humidity for 7 days, the water absorption was determined in accordance with DIN EN ISO 62:2008-05 (gravimetric method, method 4). 2 The measurement was repeated three times for a sample with a thickness of 50 μm. The arithmetic mean of the measurements was expressed as the water content in % by weight.

[0095] Water absorption capacity of desiccant:

[0096] After storing the samples for 7 days at 23° C. and 50% relative humidity, the water absorption was determined in accordance with DIN EN ISO 62:2008-05 (gravimetric method, method 4). In each case, three replicates were determined on approximately 10 g of desiccant. The arithmetic mean of the measurements is expressed as water content in % by weight.

[0097] Determination of penetration time (lag time):

[0098] The measure used to determine the service life of electronic structures is the calcium test. This is shown in Figure 1 For this purpose, a thin calcium layer 23, typically with a size of 10 x 10 mm2, is deposited on a glass plate 21 and then stored under a nitrogen atmosphere. The thickness of the calcium layer 23 is about 100 nm. To encapsulate the calcium layer 23, a layer (23 x 23 mm2) with the adhesive composition 22 to be tested is used. 2 ) and a thin glass slide 24 (35 μm, Schott) as a carrier material. For stabilization, the thin glass slide is laminated with a 100 μm thick PET film 26 by means of a 50 μm thick transfer tape 25 to obtain a visually highly transparent acrylate pressure-sensitive adhesive composition. The adhesive composition 22 is applied to the glass slide 21 in such a way that the adhesive composition 22 covers the calcium mirror 23 on all sides (AA) with a protruding edge of 6.5 mm.

[0099] The size of the Ca mirror is varied to obtain different edge widths. According to the present invention, unless otherwise specified, the adhesive composition layer 22 consists of a transparent first encapsulating adhesive composition covering the Ca mirror and a second encapsulating adhesive composition filled with a desiccant covering the peripheral edge area of ​​width AA. Due to the opaque slide 24, only the penetration through the adhesive or along the interface is measured.

[0100] The test is based on the reaction of calcium with water vapor and oxygen, as described, for example, by AGErlat et al. in the "47th Annual Technical Conference Proceedings—Society of Vacuum Coaters", 2004, pages 654-659 and by MEGross et al. in the "46th Annual Technical Conference Proceedings—Society of Vacuum Coaters", 2003, pages 89-92. Here, the transmittance of the calcium layer is monitored, which increases due to the conversion into calcium hydroxide and calcium oxide. In the described test configuration, this is carried out from the edge, so that the visible area of ​​the calcium mirror is reduced. The time until the absorbance of the calcium mirror is halved is called the service life. The method here covers both the reduction of the calcium mirror area from the edge and via point decomposition in the area, and the uniform reduction of the calcium mirror layer thickness caused by full-area decomposition.

[0101] The measurement conditions chosen were 85° C. and 85% relative air humidity. Unless otherwise stated, the specimens were adhered with a layer thickness of 25 μm of the adhesive composition over the entire area and without bubbles. The decomposition of the calcium mirror was monitored via transmittance measurement. The breakthrough time (lag time) was defined as the time required for the moisture to cover the distance AA up to the edge of the calcium mirror (see Figure 1 ). From observation of the transmittance, the breakthrough time can be read off as the intersection of a straight line through the measured values ​​in the essentially constant initial phase and a straight line through the measured values ​​with a stable slope of the transmittance (= decrease in absorbance, see Figure 2 ). The measured values ​​(in hours) are the average of three independent measurements. Figure 2 A curve obtained from measured data of a test is shown by way of example.

[0102] Molecular weight:

[0103] The molecular weight determination of the number-average molecular weight Mn and the weight-average molecular weight Mw was carried out by means of gel permeation chromatography (GPC). The eluent used was THF (tetrahydrofuran) with 0.1% by volume of trifluoroacetic acid. The measurement was carried out at 25° C. The precolumn used was PSS-SDV, 5 μ, ID 8.0mm x 50mm. For separation, the column used was PSS-SDV, 5μ, and and Each had an ID of 8.0 mm x 300 mm. The sample concentration was 4 g / l; the flow rate was 1.0 ml / min. The measurements were made against polystyrene standards.

[0104] Softening temperature

[0105] The measurement of the softening temperature of the adhesive resin is carried out by a related methodology called the Ring & Ball method and standardized according to ASTM E28.

[0106] The adhesive resin softening temperature of the resin was determined using a HRB 754 ring and ball tester from Herzog. The resin sample was first finely ground. The resulting powder was filled into a brass cylinder with a bottom opening (inner diameter of the upper part of the cylinder 20 mm, diameter of the bottom opening of the cylinder 16 mm, cylinder height 6 mm) and melted on a hot stage. The filling volume was selected so that the resin completely filled the cylinder after melting without overflowing.

[0107] The obtained sample is placed in the sample holder of HRB 754 together with the cylinder. If the adhesive resin softening temperature is between 50°C and 150°, the thermostat bath is filled with glycerol. A water bath can also be used at lower adhesive resin softening temperatures. The test ball has a diameter of 9.5mm and weighs 3.5g. According to the HRB 754 procedure, the ball is arranged above the sample in the thermostat bath and placed on the sample. 25mm below the bottom of the cylinder is the collector plate, and 2mm above the bottom of the cylinder is the grating (light blocking object). During the measurement process, the temperature increases at 5°C / minute. Within the temperature range of the adhesive resin softening temperature, the ball begins to move through the bottom opening of the cylinder until it eventually stops on the collector plate. In this position, it is detected by the grating, and the temperature of the thermostat bath is recorded at this point in time. Two measurements are performed. The adhesive resin softening temperature is the average value from two separate measurements.

[0108] MMAP and DACP

[0109] MMAP:

[0110] MMAP is the methylcyclohexane-aniline cloud point, which is determined using a modified ASTM D-5773-17e1 method. 5.0 g of the test substance (i.e. the adhesive resin sample to be investigated) are weighed into a dry test tube and 10 ml of dry aniline (CAS [62-53-3], ≥99.5%, Sigma-Aldrich #51788 or analogue) and 5 ml of dry methylcyclohexane (CAS [108-87-2], ≥99%, Sigma-Aldrich #300306 or analogue) are added. The test tube is shaken until the test substance is completely dissolved. To this end, the solution is heated to 100° C. The test tube containing the resin solution is then introduced into a ChemotronicCool cloud point measuring instrument from Novomatics and heated therein to 110° C. Cool at a cooling rate of 1.0 K / min. The cloud point is detected optically. To this end, the temperature at which the solution has a turbidity of 70% is recorded. The results are reported in ° C. The lower the MMAP value, the more aromatic the test substance is.

[0111] DAPC:

[0112] DACP is diacetone cloud point. 5.0 g of the test substance (adhesive resin sample to be checked) is weighed into a dry test tube and 5.0 g of xylene (isomer mixture, CAS [1330-20-7], ≥98.5%, Sigma-Aldrich #320579 or the like) is added. The test substance is dissolved at 130°C and then cooled to 80°C. Any escaped xylene is supplemented with additional xylene so that 5.0 g of xylene is present again. Subsequently, 5.0 g of diacetone alcohol (4-hydroxy-4-methyl-2-pentanone, CAS [123-42-2], 99%, Aldrich #H41544 or the like) is added. The test tube is shaken until the test substance is completely dissolved. To this end, the solution is heated to 100°C. The test tube containing the resin solution is then introduced into the Chemotronic Cool cloud point measuring instrument of Novomatics and heated to 110°C therein. Cooling is carried out at a cooling rate of 1.0 K / min. The cloud point is detected optically. For this purpose, the temperature at which the turbidity of the solution is 70% is recorded. The results are reported in ° C. The lower the DACP value, the more polar the test substance is.

[0113] transparency:

[0114] The transparency (transmittance) of the adhesive composition layer was measured in accordance with ASTM D1003-11 (Procedure A (Byk Haze-gard Dual Hazemeter), D65 standard light source). No correction for interface reflection loss was performed.

[0115] Haze:

[0116] Haze value describes the ratio of the transmitted light that the sample (adhesive composition layer) that is irradiated is scattered forward at a wide angle. Haze value therefore quantifies the structure in the surface or volume that interferes with clear vision. The method for measuring haze value is described in the ASTM D 1003-13 standard. The standard requires that four transmittance measurements be measured. Transmittance is calculated for each transmittance measurement. Four transmittances (Transmissionsgrade) are converted into haze percentage values. Haze value is measured with the Haze-gard Dual of Byk-GardnerGmbH.

[0117] Refractive Index:

[0118] The refractive index was determined in accordance with ISO 489 (method A, measuring wavelength 589 nm) at 20° C. and 50% relative air humidity. Cinnamon oil was used as contact liquid in the measurement.

[0119] For particles, the refractive index was determined according to ISO 489 (method B, measurement wavelength 589 nm).

[0120] Glass transition temperature (T g ):

[0121] The glass transition point (synonymously referred to as glass transition temperature) is given as the result of measurement by dynamic scanning calorimetry DDK (English: DSC) according to DIN 53 765: 1994-03 (especially sections 7.1 and 8.1, but with a uniform heating and cooling rate of 10 K / min in all heating and cooling steps (compare DIN 53 765: 1994-03; section 7.1; note 1)). The sample weighs 20 mg.

[0122] Example:

[0123] Ingredients used

[0124] Unless otherwise stated, all quantitative data in the following examples are weight percentages or parts by weight. The parts by weight here relate to the entire composition without photoinitiator and without solvent. The amount of photoinitiator is related to the amount of epoxy resin used (expressed as weight percentage).

[0125] SibStar 62M: SiBS (polystyrene block-polyisobutylene block copolymer) from Kaneka with a block polystyrene content of 20% by weight. w = 60.000 g / mol, the glass transition temperature of the polystyrene block is 100°C and that of the polyisobutylene block is -60°C.

[0126] Uvacure 1500: Cytec's alicyclic diepoxide (3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylic acid), with a viscosity of about 300 mPas at 23°C

[0127] Regalite R1100: Eastman's fully hydrogenated hydrocarbon resin (ring and ball softening temperature 100°C, DACP = 71°C, MMAP = 76°C)

[0128] TerPIB 950: Polyisobutylene from TerHell with a weight-average molecular weight of 950 g / mol

[0129] Triarylsulfonium hexafluoroantimonate: A cationic photoinitiator from Sigma-Aldrich. This photoinitiator has a maximum absorption in the range of 320 nm to 360 nm and is present in the form of a 50 wt% solution in propylene carbonate.

[0130] Caloxol CP2: Calcium oxide from Omya Chemicals, water absorption of about 40% by weight

[0131] Hydrotalcit: Synthetic hydrotalcite (Mg6Al2(CO3)(OH) from Sigma-Aldrich 16 4H2O, product number 652288), dried in a convection oven at 200°C for 8 hours, water absorption of about 12% by weight

[0132] 2-(3,4-Epoxycyclohexyl)ethyltriethoxysilane (TEE): triethoxysilane with alicyclic epoxy groups, water absorption (3 mol of water per 1 mol of TEE) 19 wt%

[0133] Preparation of a pressure-sensitive adhesive composition as a transparent first adhesive composition

[0134] Two formulations for a transparent first pressure-sensitive adhesive composition according to the invention are listed in Table 1 (the amount of photoinitiator is related to the amount of epoxy resin used; the information is given as weight percent relative to the epoxy resin).

[0135]

[0136] Table 1

[0137] An activatable encapsulating pressure-sensitive adhesive composition (T1) and a desiccant-filled pressure-sensitive adhesive (T2) were prepared. The refractive index of the encapsulating pressure-sensitive adhesive composition T2 without hydrotalcite was determined to be 1.53, and the refractive index of the hydrotalcite was determined to be 1.51.

[0138] The organic components were dissolved in a mixture of toluene (300 parts), acetone (150 parts) and special boiling point mineral spirits 60 / 95 (550 parts) at room temperature to form a 50 wt% solution. The photoinitiator triarylsulfonium hexafluoroantimonate or hydrotalcite was then added to the solution.

[0139] The formulation was coated from solution onto a siliconized PET liner as carrier layer using a doctor blade method and dried at 120° C. for 15 minutes. The thickness of the dried pressure-sensitive adhesive composition was 25 μm. The sample was covered with another siliconized but more easily releasable PET liner as top layer.

[0140] Preparation of adhesive composition as desiccant-filled second adhesive composition

[0141] Three formulations for the second adhesive composition filled with desiccant according to the invention and three comparative adhesive compositions are listed in Table 2. The pressure-sensitive adhesive compositions according to the invention are two pressure-sensitive adhesive compositions (PSA1 and PSA2) and a liquid adhesive composition filled with desiccant (LA1). The amount of photoinitiator is related to the amount of epoxy resin used (the information is given in weight percentage relative to the epoxy resin).

[0142]

[0143] Table 2

[0144] In the case of the pressure-sensitive adhesive composition, the desiccant-filled second adhesive composition was prepared and dried as described for the transparent first pressure-sensitive adhesive composition. The same was true for the comparative adhesive composition. The preparation of the liquid adhesive composition LA1 was carried out by dispersing triarylsulfonium hexafluoroantimonate and calcium oxide in Uvacure at room temperature.

[0145] A medium pressure mercury lamp with a minimum of 400 mJ / cm 2 The activatable adhesive composition to which a photoinitiator is added is cured with a UV-C dose of 1000 nm. In the present application, the information on transparency, haze and breakthrough time always relates to the cured adhesive composition layer once curing has taken place.

[0146] For the adhesive compositions, the penetration times for different edge widths were determined (Table 3), wherein the entire area of ​​the adhesive composition layer 22 was made of the relevant adhesive composition here, since only the material parameters were intended to be determined. The desiccant-filled liquid adhesive LA1 was applied here with a thickness of 15 μm by adding some monodisperse PMMA spheres, the other adhesives were applied with a thickness of 25 μm.

[0147]

[0148] Table 3

[0149] A comparison of the opaque, highly desiccant-filled second adhesive composition (PSA1, PSA2, LA1) according to the present invention with the desiccant-filled adhesive composition (V1, V2) or the unfilled barrier adhesive composition (V3) according to the prior art clearly demonstrates the superior barrier effect of the highly filled, non-transparent adhesive composition.

[0150] Figure 3 The penetration time is shown for an edge width of 1 mm as a function of the water-removing agent content (i.e., the desiccant content, here CaO), wherein the entire surface 22 is likewise made of an adhesive composition similar to the adhesive composition PSA2 (with a modified desiccant content). It is noteworthy that a technically usable penetration time can only be achieved from a desiccant content of 15% by weight. This occurs in conjunction with a water absorption of the second adhesive composition of more than 5% by weight.

[0151] Furthermore, the following structures with an edge width AA of 2 mm were prepared for the service life test:

[0152] Example First adhesive composition Second adhesive composition Delay time [h] B1 T1 PSA1 71 B2 T1 PSA2 415 B3 T2 PSA1 52 B4 T2 PSA2 369 B5 T1 LA1 1290 B6 T2 LA1 1309 VB1 T1 V2(=T1) 33 VB2 T2 V1 36 VB3 T1 V3 19

[0153] Table 4

[0154] Here (like all other adhesive layers) a desiccant-filled liquid adhesive layer LA1 was produced with a thickness of 25 μm, the first adhesive composition serving as a spacer. The adhesive composition that squeezed out from the sides during the joining process was removed.

[0155] The penetration times determined in the respective cases are listed in Table 4. As expected, these are generally lower than the values ​​for the full-area coatings with the second adhesive composition filled with desiccant, which can be attributed to processing tolerances and errors. However, according to the invention, there is a clear advantage compared to the full-area encapsulation with the transparent first adhesive composition. Thus, for a 50% increase in the calcium oxide content in the second adhesive composition (PSA1 vs. V1), the penetration time increases by about 100%, which also demonstrates a synergistic effect at a desiccant filling of more than 15% or a water absorption of more than 5% by weight.

[0156] As a result of the arrangement according to the invention, the active area of ​​the electronic arrangement remains transparently encapsulated and the edge region is sealed in an improved manner by the adhesive composition which is highly filled with desiccant.

Claims

1. A method for protecting an organic electronic device arranged on a substrate, comprising the steps of: - applying a first adhesive to the electronic device or the cover; - applying a second adhesive around the electronic device; - applying a cover over the organic electronic device such that the organic electronic device is at least partially covered; - gluing the cover with at least one layer of a first adhesive and at least one layer of a second adhesive, It is characterized in that - at least one layer of the first adhesive at least partially covers the organic electronic device and has a transparency greater than 80% and a haze less than 5%; and at least one layer of the second adhesive surrounds at least one layer of the first adhesive on the periphery of the at least one layer of the first adhesive, so that the at least one layer of the second adhesive forms an edge encapsulation, wherein the width of the edge encapsulation using the second adhesive does not exceed 2 mm, and wherein the second adhesive has a water absorption capacity of more than 5% by weight, The first adhesive contains less than 2% by weight of a particulate desiccant.

2. The protection method according to claim 1, characterized in that: The second adhesive has a water absorption capacity greater than 10% by weight.

3. The protection method according to claim 2, characterized in that: The second adhesive has a water absorption capacity greater than 14% by weight.

4. The protection method according to claim 1, characterized in that: The refractive index difference between the first adhesive and the desiccant is no greater than 0.

02.

5. The protection method according to claim 4, characterized in that: The first adhesive contains hydrotalcite and / or a molecularly dispersed desiccant.

6. The protection method according to any one of claims 1 to 5, characterized in that: The second adhesive contains a desiccant.

7. The protection method according to claim 6, characterized in that: The desiccant in the second adhesive is calcium oxide.

8. The protection method according to any one of claims 1 to 5, characterized in that: The first adhesive is applied in the form of a tape.

9. The protection method according to any one of claims 1 to 5, characterized in that: The second adhesive is applied in the form of a liquid adhesive.

10. The protection method according to any one of claims 1 to 5, characterized in that: The first adhesive and the second adhesive have the same base adhesive composition.

11. The protection method according to any one of claims 1 to 5, characterized in that: The second adhesive is applied at a distance from the organic electronic device.

12. Organic electronic structures, including - substrate, - an organic electronic device arranged on said substrate, a cover which at least partially covers the organic electronic device and is adhered at least in certain areas to the substrate and / or the electronic device, It is characterized in that The structure also includes: - at least one layer of a first adhesive at least partially covering the organic electronic device and having a transparency greater than 80% and a haze less than 5%, at least one layer of a second adhesive which surrounds at least one layer of the first adhesive on its periphery, so that the at least one layer of the second adhesive forms an edge encapsulation, wherein the width of the edge encapsulation using the second adhesive does not exceed 2 mm, and wherein the second adhesive has a water absorption capacity of more than 5% by weight, The first adhesive contains less than 2% by weight of a particulate desiccant.

13. The organic electronic structure according to claim 12, characterized in that: The second adhesive has a water absorption capacity greater than 10% by weight.

14. The organic electronic structure according to claim 13, characterized in that: The second adhesive has a water absorption capacity greater than 14% by weight.

15. The organic electronic structure according to any one of claims 12 to 14, characterized in that: The second adhesive contains a desiccant.

16. The organic electronic structure according to claim 15, characterized in that: The desiccant in the second adhesive is calcium oxide.

17. The organic electronic structure according to any one of claims 12 to 14, characterized in that: The first adhesive contains hydrotalcite and / or a molecularly dispersed desiccant as a desiccant.

18. The organic electronic structure according to any one of claims 12 to 14, characterized in that: The first adhesive and the second adhesive have the same base adhesive composition.

19. The organic electronic structure according to any one of claims 12 to 14, characterized in that: The cover completely covers the electronic device.

20. The organic electronic structure according to any one of claims 12 to 14, characterized in that: The layer of the second adhesive completely surrounds the organic electronic device.

21. The organic electronic structure according to any one of claims 12 to 14, characterized in that: The second adhesive is applied at a distance from the organic electronic device.

22. The organic electronic structure according to any one of claims 12 to 14, characterized in that: There are no further polymer layers between the cover and the organic electronic device, ie only the at least one layer of the first adhesive acts as a polymer layer and no further layers are present.

23. The organic electronic structure according to any one of claims 12 to 14, characterized in that: The organic electronic device arranged on the substrate is already provided with a primary package.

24. The organic electronic structure according to any one of claims 12 to 14, characterized in that: The at least one layer of the first adhesive completely covers the organic electronic device.

25. The organic electronic structure according to claim 21, characterized in that The second adhesive is applied at a distance of 0.1 mm to 2 mm relative to the organic electronic device.

26. The organic electronic structure according to claim 25, characterized in that The second adhesive is applied at a distance of 0.2 mm to 1 mm relative to the organic electronic device.

27. The organic electronic structure according to claim 25, characterized in that: The second adhesive is applied at a distance of 0.2 mm to 0.5 mm relative to the organic electronic device.

28. The organic electronic structure according to claim 21, characterized in that The distance is filled with the first adhesive.

29. The organic electronic structure according to any one of claims 12 to 14, characterized in that The thickness of the adhesive layer of the first or second adhesive is between 4 μm and 250 μm.

30. The organic electronic structure according to claim 29, characterized in that The thickness of the adhesive layer of the first or second adhesive is not more than 50 μm.

31. The organic electronic structure according to claim 29, characterized in that The thickness of the adhesive layer of the first or second adhesive is not more than 25 μm.

32. The organic electronic structure according to any one of claims 12 to 14, characterized in that The first adhesive is a pressure-sensitive adhesive.

33. The organic electronic structure according to claim 32, characterized in that: The first adhesive is an activatable pressure-sensitive adhesive.

34. The organic electronic structure according to claim 32, characterized in that: The first adhesive is present as a pressure-sensitive tape.

35. The organic electronic structure according to any one of claims 12 to 14, characterized in that The second adhesive is a pressure-sensitive adhesive composition.

36. The organic electronic structure according to claim 35, characterized in that The second adhesive is designed as a pressure-sensitive adhesive tape.

37. The organic electronic structure according to claim 35, characterized in that The second adhesive is configured as a liquid adhesive.

38. The organic electronic structure according to claim 15, characterized in that The second adhesive has a desiccant content of 15 wt % or more.

39. The organic electronic structure according to claim 38, characterized in that The second adhesive has a desiccant content of 30 wt % or more.

40. The organic electronic structure according to claim 37, characterized in that The second adhesive has a desiccant content of 40 wt % or more.

41. The organic electronic structure according to claim 12 or 13, characterized in that: The granular desiccant is calcium oxide.

42. The organic electronic structure according to claim 18, characterized in that The base adhesive composition has a relative humidity of less than 100 g / m 2 Water vapor transmission rate d, based on a layer thickness of 50 μm.

43. The organic electronic structure according to claim 42, characterized in that The base adhesive composition has a viscosity of less than 20 g / m at 38° C. / 90% relative humidity. 2 d water vapor transmission rate.

44. The organic electronic structure according to claim 42, characterized in that The base adhesive composition is a polybutylene-based adhesive composition.

45. The organic electronic structure according to any one of claims 12 to 14, characterized in that The first adhesive is applied as a sheet-like structure, and the second adhesive is applied as a liquid adhesive.

Citation Information

Patent Citations

  • Method for encapsulating an electronic arrangement

    DE102008047964A1

  • Reactive 2-component adhesive system in film form

    DE102013222739A1

  • Method for encapsulation of an electronic assembly

    EP2166593A1

  • Method for encapsulation of an electronic assembly

    EP2200105A2

  • Method for encapsulating an electronic arrangement

    EP2279537B1